Interventional radiology: Role in the treatment of sarcomas. (May 2018) - de Baere, Thierry; Tselikas, Lambros; Gravel, Guillaume; Hakime, Antoine; Deschamps, Frederic; Honoré, Charles; Mir, Olivier; Lecesne, Axel
Abstract: In bone and soft tissue sarcomas (STS), surgery was to the only local curative treatment, but recently, radiation therapy and interventional radiology has evolved to potentially curative treatment, namely in small size tumours. Indication for local treatment in STS needs validation in multidisciplinary team. Most will agree on local treatment for single metastatic location in a well-controlled disease and for no local treatment in a rapidly evolving multi-metastatic disease. The challenge is in patients who are in between, for whom benefit of disease control on overall survival should be evaluated. Local treatment has been reported beneficial in some large retrospective series, regardless of the association with chemotherapy in selected patients with oligometastatic disease. Recent technical innovation in image guidance allows to deliver local treatment through needles inserted percutaneously, and image-guided thermal ablation of small tumour is now part of the treatment armamentarium in selected oligometastatic diseases, allowing for local destruction of small tumour. Radiofrequency ablation allows to control small size STS lung metastases in roughly 90% of attempts, thus providing an efficient and low-invasive local control with preservation of organ function. Small size bone deposit can be targeted with the same rate of efficacy when tumours are small. Ablation can be used in the liver when some tumour foci become resistant to systemic therapy, namely in gastrointestinal stromal tumour patients. In addition, interventional radiology can now provide efficient and rapid pain palliation as well as bone reconstruction with the use of cementoplasty and percutaneous osteosynthesis, alongside radiation therapy which has been a long time player for pain palliation in bone metastases. Highlights: Image-guided thermal ablation allows for local control of small tumour. Radiofrequency ablation allows to control small size soft tissue sarcomas lung metastases in 90% of attempts. Image-guided thermal ablation provides a low-invasive and repeatable treatment with preservation of organ function. Cementoplasty within osteolytic metastases provides pain reduction in 80–97% of cases.